An L-RNA Aptamer that Binds and Inhibits RNase. Issue 11 (19th November 2015) - Olea, Charles; Weidmann, Joachim; Dawson, Philip E.; Joyce, Gerald F.
Summary: L-RNA aptamers were developed that bind to barnase RNase and thereby inhibit the function of the enzyme. These aptamers were obtained by first carrying out in vitro selection of D-RNAs that bind to the full-length synthetic D-enantiomer of barnase, then reversing the mirror and preparing L-RNAs of identical sequence that similarly bind to natural L-barnase. The resulting L-aptamers bind L-barnase with an affinity of ∼100 nM and function as competitive inhibitors of enzyme cleavage of D-RNA substrates. L-RNA aptamers are resistant to degradation by ribonucleases, thus enabling them to function in biological samples, most notably for applications in molecular diagnostics and therapeutics. In addition to the irony of using RNA to inhibit RNase, L-RNA aptamers such as those described here could be used to measure the concentration or inhibit the function of RNase in the laboratory or in biological systems. Graphical Abstract: Highlights: L-RNA aptamers were selected that bind and inhibit barnase RNase This required synthesizing the full-length synthetic D-enantiomer of barnase The L-RNA aptamers are competitive inhibitors of degradation of D-RNA substrates The first time a mirror-image aptamer has been raised against an entire enzyme Abstract : Olea et al. select mirror-image RNA molecules, composed of the non-natural L-isomer, for their ability to bind and inhibit RNase, an enzyme that rapidly degrades natural RNA. This was accomplished by selecting natural RNAs that bind the full-length, non-natural isomer of RNase then reversing the mirror to enable L-RNA to protect its natural counterpart.